Inducing a Functional-Pharmacological Coupling in the Human Brain to Achieve Improved Drug Effect - Sar-El, Roy; Sharon, Haggai; Lubianiker, Nitzan; Hendler, Talma; Raz, Gal (Frontiers in Neuroscience, 2020)
Neuropharmacotherapy is substantially hindered by poor drug targeting, resulting in low specificity and efficacy. Here, we tested a novel, non-invasive targeting approach (termed functional-pharmacology), which couples drug administration with a task that activates the drug’s sites-of-action in the brain. This technique possibly improves the specificity of drug delivery and its efficacy via neurovascular coupling processes that result in increased local blood flow. We examined this notion in two studies in which Methylphenidate (MPH) was administered to neurotypical adults and to subjects with ADHD. In study 1 we employed a within-subject factorial design and found that only following MPH administration, subjects that performed better in the cognitive induction task showed greater improvements in N-back performance. Moreover, only under MPH-Cognitive induction condition, this improvement correlated with concurrent N-Back rDLPFC activation. In Study 2, subjects with ADHD performed better on sustained attention when MPH administration was followed by a cognitive challenge rather than a control task. Again, those who were more attentive to the cognitive challenge scored higher. Our results support the functional-pharmacology concept feasibility and efficacy, hence opening a new horizon for patient-tailored, context-driven drug therapy.